Counseling on The Implementation of Gymnastics for Pregnant Women in Undergoing a Healthy Pregnancy and Readiness for Normal Childbirth For Pregnant Women - Hariati, Mayang Citra; siregar, Wilda Wahyuni (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Institut Kesehatan Medistra Lubuk Pakam, 2024)
The health of pregnant women is still one of the indicators of how to achieve the degree of public health in Indonesia. Pregnant women who have a healthy and comfortable pregnancy will of course have an impact on safe childbirth and also the baby born will be healthier, to realize this, pregnant gymnastics can be done for pregnant women because it can have a real health impact felt on the mother during pregnancy and even until childbirth. The purpose of this community service is to strive for pregnant women to be able to have a healthy pregnancy and prepare the mother's body to give birth safely and smoothly. Other goals of pregnancy gymnastics are Achieving optimal relaxation during pregnancy until childbirth both physically and psychologically, Achieving the adequacy of the pelvic floor muscles when straining, Preparing the pregnant woman mentally and physically and Achieving physiological, natural, comfortable childbirth, with the mother and her baby. The implementation of this community service activity was carried out at the Cahaya 2 Sekip Clinic, for one day on March 23, 2024 with a total of 24 respondents of pregnant women whose gestational age is in the second trimester and third trimester of pregnancy. The implementation also consists of the stage of collecting data on pregnant women, determining the time of activities, initial examination of pregnant women, counseling activities in the form of education about pregnancy gymnastics and the last stage, namely the implementation of pregnancy gymnastics activities. As a result of this activity, almost all pregnant women do pregnancy gymnastics well, besides that pregnant women are also very enthusiastic and happy with the pregnancy gymnastics activity because repondents can share with extension workers and other participants and especially pregnant gymnastics has many benefits for mothers during pregnancy.